Introduksi mesin pengolahan sagu untuk meningkatkan produksi pati di Kampung Sidey Makmur: Introduction of sago processing machines to enhance starch production in Sidey Makmur Village, Sidey District, Manokwari Regency - Situngkir, Risma U.; Darma, Darma; Reniana, Reniana (Fakultas Peternakan Universitas Papua, 2026)
ABSTRACT Small-scale community-based sago processing in West Papua has high potential, but production at the household level remains limited due to manual processing practices. This community service program aimed to strengthen household sago processing capacity in Sidey Makmur Village, Sidey District, Manokwari Regency through the introduction of a semi-mechanical processing system using a cylinder-type rasping machine (variant-02), training, and on-site technical mentoring. Program performance was evaluated through direct observation of partner operation and production outcomes. The intervention reduced processing time to about 15.5 hours per tree (1 tree per 2 days), achieved rasping capacity of 490 kg/hour, and increased fresh sago starch production from 180 kg/week to 524 kg/week. The results indicate that appropriate technology transfer improves production efficiency, supports operational skill development among partners, and opens greater opportunities for local income improvement. Keywords: community service; Manokwari Regency; sago starch; semi-mechanical processing; technology transfer ABSTRAK Pengolahan sagu skala rumah tangga berbasis masyarakat di Papua Barat memiliki potensi besar, namun produktivitasnya masih terbatas karena proses yang dominan manual. Program pengabdian ini bertujuan meningkatkan kapasitas pengolahan sagu di Kampung Sidey Makmur, Distrik Sidey, Kabupaten Manokwari melalui introduksi sistem pengolahan semi-mekanis menggunakan mesin pemarut tipe silinder varian-02, pelatihan, dan pendampingan teknis di lapangan. Evaluasi dilakukan melalui observasi langsung terhadap pengoperasian mesin dan capaian produksi mitra. Hasil kegiatan menunjukkan waktu pengolahan sekitar 15,5 jam per pohon (1 pohon per 2 hari), kapasitas pemarutan 490 kg/jam, serta peningkatan produksi pati sagu segar dari 180 kg/minggu menjadi 524 kg/minggu. Kegiatan ini menunjukkan bahwa alih teknologi tepat guna dapat meningkatkan efisiensi proses, memperkuat keterampilan operasional mitra, dan membuka peluang peningkatan pendapatan masyarakat. Kata kunci: Alih Teknologi; Kabupaten Manokwari; Pati Sagu; Pengabdian Masyarakat; Pengolahan Semi-Mekanis